Separation and Washing of Candida Cells from White Blood Cells Using Viscoelastic Microfluidics - Hyunjung Lim; Jae Young Kim; Seunghee Choo; Changseok Lee; Byoung Joe Han; Chae Seung Lim; Jeonghun Nam (Micromachines, 2023)
An early and accurate diagnosis of Candida albicans is critical for the rapid antifungal treatment of candidemia, a mortal bloodstream infection. This study demonstrates viscoelastic microfluidic techniques for continuous separation, concentration, and subsequent washing of Candida cells in the blood. The total sample preparation system contains two-step microfluidic devices: a closed-loop separation and concentration device and a co-flow cell-washing device. To determine the flow conditions of the closed-loop device, such as the flow rate factor, a mixture of 4 and 13 μm particles was used. Candida cells were successfully separated from the white blood cells (WBCs) and concentrated by 74.6-fold in the sample reservoir of the closed-loop system at 800 μL/min with a flow rate factor of 3.3. In addition, the collected Candida cells were washed with washing buffer (deionized water) in the microchannels with an aspect ratio of 2 at a total flow rate of 100 μL/min. Finally, Candida cells at extremely low concentrations (Ct > 35) became detectable after the removal of WBCs, the additional buffer solution in the closed-loop system (Ct = 30.3 ± 1.3), and further removal of blood lysate and washing (Ct = 23.3 ± 1.6).